2018
DOI: 10.2147/dddt.s158888
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of betahistine mesilate tablets as augmentation for oxcarbazepine and carbamazepine in treating vestibular paroxysmia

Abstract: BackgroundVestibular paroxysmia (VP) is a rare episodic peripheral vestibular disorder. This study was conducted to compare the efficacy and acceptability of carbamazepine (CBZ) plus betahistine mesilate tablets (BMT) (CBZ+BMT) and oxcarbazepine (OXC) plus BMT (OXC+BMT) in treating VP, and investigated whether the synergistic effect could be increased along with the increased dose of BMT.MethodsVP patients were recruited and randomly assigned to receive CBZ+BMT or OXC+BMT. The doses of CBZ and OXC were set to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Bayer et al found a relative risk of 0.67 ( p = 0.025) for experiencing one or more VP attacks with oxcarbazepine treatment compared to placebo (7). Other studies have shown that betahistine mesilate tablets may improve the effectiveness and acceptability of carbamazepine and oxcarbazepine treatment in patients with VP (10,11). In our study we only looked at the effect of carbamazepine as experienced by patients and found that a slight majority (58%) of those that (had) used this medication reported a positive perceived effect.…”
Section: Discussionmentioning
confidence: 99%
“…Bayer et al found a relative risk of 0.67 ( p = 0.025) for experiencing one or more VP attacks with oxcarbazepine treatment compared to placebo (7). Other studies have shown that betahistine mesilate tablets may improve the effectiveness and acceptability of carbamazepine and oxcarbazepine treatment in patients with VP (10,11). In our study we only looked at the effect of carbamazepine as experienced by patients and found that a slight majority (58%) of those that (had) used this medication reported a positive perceived effect.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the course of the disease in 32 patients over 3 years showed a significant and consistent reduction in episode frequency, which fell to 10% of the initial value, as well as a reduction in the intensity and duration of episodes [44]. Xue et al conducted a clinical study using OXC together with betahistine mesylate (BMT) in patients with hypersensitivity to CBZ; the results showed increased efficacy of this combination compared to monotherapy with OXCs [54]. Yi et al in a retrospective study on the support of BMT therapy with OXC in patients with paroxysmia also demonstrated the greater efficacy of this regimen [55].…”
Section: Pharmacological Treatmentmentioning
confidence: 99%